Niveles de colesterol en pobladores de ambos sexos del centro poblado El Carmelo de la provincia de Virú, departamento La Libertad. julio – 2012” - Iturbe Cabanillas, Víctor Ricardo (2012)
In this paper discloses the results of the determination of cholesterol on 77 adult male and female residents of the Village Center of Carmel Viru Province in July 2012, between the ages of 18-65 years, for which took blood samples and underwent the respective analysis method enizmático (Hydrolysis-oxidase), thus determining the cholesterol level of each resident. The objective was to determine the frequency of people with cholesterol values decreased, normal and normal upper limit. For the interpretation of results was used to calculate percentage by division by sex and age, and the level of cholesterol decreased, normal and normal upper limit. The 76.62% of the residents had decreased plasma cholesterol values, the normal values were 12.98% and 10.39% had normal values at the upper limit. By age, the highest percentage of decreased levels (38.16%) constituted the sample of people whose ages ranged between 18-35 years, while the highest percentage of normal and normal levels at the upper limits (9.09%) were between the age range of 36-50 years and 51-65 years. We conclude that the study population has no risk of hypercholesterolemia